Relatives. Issue 5 (September 2022) - Martinez, Deniss
This poem is a recollection of my own childhood. It is a reconnecting and remembering of the many lessons I learned from plant relatives and a reflection of how traditional medicines heal us and hold us both physically and emotionally. I use the framing of relatives that comes from other Indigenous scholars' frameworks of relationality and kincentricity. These understandings of being in relationship emphasize the importance of nonhuman relatives not just as a health or food resource but as a relative with which to engage in reciprocal relationships with. These relationships transform us, they raise us, and they heal us. To view the original version of this poem, see the supplemental material section of this article online.